Evaluation of D'Amico criteria for low-risk prostate cancer. (August 2013) - Milonas, Daimantas; Kinčius, Marius; Skulčius, Giedrius; Matjošaitis, Aivaras Jonas; GudinavičienĖ, Inga; Jievaltas, Mindaugas
Abstract Objective. The aim of the study was to identify the risk of unfavourable disease (≥ pT3 and/or Gleason score ≥ 7) in radical prostatectomy (RP) specimens and biochemical progression-free survival (BPFS) after RP in patients with low-risk prostate cancer detected by D'Amico criteria before surgery. Material and methods. Between 2004 and 2007, 690 men underwent prostate biopsy and RP at a single university hospital. Of those, 248 patients (35.9%) had low-risk prostate cancer criteria. The endpoints of the study were detection of low-risk (pT2 and Gleason score ≤ 6) or unfavourable (≥ pT3 and/or Gleason score ≥ 7) prostate cancer, and BPFS. The risk of progression was analysed using multivariate Cox regression model and BPFS was established using Kaplan–Meier analysis. Results.The median follow-up was 60 months (1–112 months). pT3 was detected in 14.1%, and Gleason score ≥ 7 in 32.7% of patients. Unfavourable prostate cancer was detected in 37.5% of patients. Overall biochemical relapse rate was 13.6%. The estimated probability of 3-, 5- and 8-year BPFS for all study patients was 90.6%, 88.1% and 77.9%, respectively. Eight-year BPFS was 83.3% for low-risk prostate cancer and 68.2% for unfavourable prostate cancer (p = 0.007). Positive surgical margins (p = 0.0001) and postoperative Gleason score (p = 0.023) were the most significant predictors of biochemical relapse in Cox regression analysis. Conclusions.The D'Amico criteria may underestimate potentially aggressive prostate cancer in up to 37.5% of patients. Consequently, caution is recommended when the decision concerning the treatment modality is based on D'Amico criteria alone.